Habitat Characteristics and Population Structure of Bamboo Shells (Solen lamarckii, Chenu 1984) in the Intertidal Zone of Apiapi Village, Bandar Laksamana District Bengkalis - Ulfa, Marya; Nasution, Syafruddin; Tanjung, Afrizal (Jurnal Perikanan dan Kelautan, 2020)
The study about habitat characteristics and population structure razor clam (Solen lamarckii, Chenu 1984) in intertidal zone Apiapi Village Bandar Laksamana District Bengkalis Regency conducted on January 2020. The purpose of this study was to analyze about habitat characteristics and population structure of razor clam and the correlation between substrate particle size and population density of razor clam. The habitat parameters measured include the physical and chemical parameters of sea waters. Determination of the station using purposive sampling method. Razor clam samples were collected by using a 1 x 1 m2 frame that laid along a transect. There were 4 plots and 3 subplots along the transect as replications. The result showed, the sediment tipe was sandy substrate, organic material was low, total suspended solid was high. Population density of razor clams was 3.3-23.3 Ind/m2. The distribution pattern of razor clams through each plot was uniform. While, the most common size of razor clam 5.04-5.62 cm. The correlation between particle size and population density of razor clam was strong